Potential Loss From Parking Levies - Sari, Vita Fitria; Cheisviyanny, Charoline; Deviani, Deviani (Politeknik Keuangan Negara STAN, 2023)
The existence of abundant illegal parking attendants in the city of X causes a leakage of parking revenue. The phenomenon of loss in parking levies encourages us to conduct this research. This research is an exploratory research with a quantitative descriptive approach to calculate the potential of parking loss in X city. Data were collected through interview and observation which never been done. We interviewed illegal parking attendants from 4 sub-districts by using convenience sampling which never been used before. This study found that the optimal potential of parking levies in a year reached IDR 8.682.868.820,- while the average realization of parking levies within five years was only IDR 1.427.539.500.- per year. This means that only 16.44% of potential parking levies are realized in a year. So there are still 83.56% potential parking levies haven't been recognized. It shows that local governments have not been able to identify the number of potential parking levies and impress parking mismanagement.